Renal Failure Associated with APECED and Terminal 4q Deletion: Evidence of Autoimmune Nephropathy - Mohammed Al-Owain; Namik Kaya; Hamad Al-Zaidan; Ibrahim Bin Hussain; Hadeel Al-Manea; Hindi Al-Hindi; Shelley Kennedy; M. Anwar Iqbal; Hamad Al-Mojalli; Albandary Al-Bakheet; Anne Puel; Jean-Laurent Casanova; et al. (Clinical and Developmental Immunology)
Autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy (APECED) is a rare autosomal recessive disorder caused by mutations in the autoimmune regulator gene (AIRE). Terminal 4q deletion is also a rare cytogenetic abnormality that causes a variable syndrome of dysmorphic features, mental retardation, growth retardation, and heart and limb defects. We report a 12-year-old Saudi boy with mucocutaneous candidiasis, hypoparathyroidism, and adrenocortical failure consistent with APECED. In addition, he has dysmorphic facial features, growth retardation, and severe global developmental delay. Patient had late development of chronic renal failure. The blastogenesis revealed depressed lymphocytes' response to Candida albicans at 38% when compared to control. Chromosome analysis of the patient revealed 46,XY,del(4)(q33). FISH using a 4p/4q subtelomere DNA probe assay confirmed the deletion of qter subtelomere on chromosome 4. Parental chromosomes were normal. The deleted array was further defined using array CGH. AIRE full gene sequencing revealed a homozygous mutation namely 845_846insC. Renal biopsy revealed chronic interstitial nephritis with advanced fibrosis. In addition, there was mesangial deposition of C3, C1q, and IgM. This is, to the best of our knowledge, the first paper showing evidence of autoimmune nephropathy by renal immunofluorescence in a patient with APECED and terminal 4q deletion.